P79 Do children describe the benefits of inhaled asthma therapy in the same way as adults?. (2nd December 2011) - Gilchrist, F J; Brady, M; Gallop, K; Wild, D J; Tabberer, M; Jacques, L; Lenney, W
Abstract : Introduction: Although it is well reported in adults, there is relatively little data on how children with asthma and their parents describe their attitudes to the disease, expectations of therapy and perception of treatment benefit. Our aim was to investigate this and determine if they differed from reports by adults with asthma. We plan to use the results to refine patient reported outcome measures for children with asthma. Methods: We recruited families with an asthmatic child (4–11 years) who had recently been prescribed a change in treatment (starting inhaled corticosteroid monotherapy (ICS) or changing from ICS to inhaled corticosteroid/long acting ß2 agonist combination therapy (ICS/LABA). Semi-structured interviews were conducted with the parents and the children if aged 7–11 years. Transcripts were analysed using a combination of thematic and content analysis and recruitment discontinued in each group once data saturation was reached. Results: We undertook 41 interviews including 28 parents and 13 children. The numbers in each group can be seen in Abstract P79 table 1 . All the children on ICS/LABA had been changed as their symptoms were not controlled on ICS monotherapy. The interviews highlighted the significant effects that paediatric asthma has on the whole family and the distress the symptoms cause to the child and their parents. Exacerbations led to frequent school absence and associated time off work for the parents. Both parents and children hoped that the new medication would lead to better symptom control, increased participation in physical activities and decreased visits to the GP or hospital. Positive effects of treatment change were identified, particularly in those changing from ICS to ICS/LABA. Benefits described included improvement in symptoms (especially cough and wheeze), increased participation in sport or play activities and reduced rescue medication use. These effects resulted in few visits to the GP/hospital and better attendance at school. Conclusions: While asthma symptoms prevent adults and children from participating in different types of activities (eg, school not employment), children and their parents report the same concepts as adult patients with asthma.